The once and future sex : going medieval on women's roles in society - Janega, Eleanor (W. W. Norton & Company, Inc., 2023)
In this vibrant, high-spirited history, medievalist Eleanor Janega turns to the Middle Ages to unfurl its suppositions about women and reveal what's shifted over time--and what hasn't. Enshrined medieval thinkers, almost always male, subscribed to classical Greek and Roman philosophy and Christian theology for their concepts of the sexes, deriding women as oversexed sinners, inherently lustful, insatiable, and weak. In contrast, drawing on accounts of medieval women like Eleanor of Aquitaine and Hildegard of Bingen, Janega shows us how real women of the era lived. -- adapted from jacket